2017
DOI: 10.1016/j.agee.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Diet management to effectively abate N 2 O emissions from surface applied pig slurry

Abstract: Application of manure (uriñe and/or feces) to agricultural soils enhances emissions of gases such as nitrous oxide (N 2 0) and carbón dioxide (C0 2 ). Some minor N compounds such as hippuric acid and benzoic acid present in uriñe can be controlled through diet manipulation to mitígate these emissions. The aim of this study was to evalúate how the inclusión of fibrous by-products in the diet of pigs affects hippuric and benzoic acid concentrations in the excreted urine/slurry, and their possible effect on N 2 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
(41 reference statements)
5
10
0
1
Order By: Relevance
“…The current results show that the total excretion of benzoic and hippuric acids increased from 1.05 mg/mL in the control diet to 2.38 mg/mL in the 200 g/kg OC diets, in parallel to increasing levels of intake, absorption and excretion of polyphenols and fibre. These values are within the range of values reported in the literature for growing pigs using fibrous ingredients (Sánchez-Martín et al, 2017), but are lower than in ruminants, where hippuric acid accounts for about 5% of the N excreted (Bristow et al, 1992, Bussink andOenema, 1998). Recent studies have demonstrated that both benzoic and hippuric acids may inhibit nitrification in soils, and therefore reduce nitrous oxide emissions from slurry applied to soil (Kool et al, 2006;Sánchez-Martín et al, 2017), which seems to be related with changes in pH and the corresponding reduction of NH 3 emission.…”
Section: Nutrient Balance and Effluent Compositionsupporting
confidence: 79%
See 1 more Smart Citation
“…The current results show that the total excretion of benzoic and hippuric acids increased from 1.05 mg/mL in the control diet to 2.38 mg/mL in the 200 g/kg OC diets, in parallel to increasing levels of intake, absorption and excretion of polyphenols and fibre. These values are within the range of values reported in the literature for growing pigs using fibrous ingredients (Sánchez-Martín et al, 2017), but are lower than in ruminants, where hippuric acid accounts for about 5% of the N excreted (Bristow et al, 1992, Bussink andOenema, 1998). Recent studies have demonstrated that both benzoic and hippuric acids may inhibit nitrification in soils, and therefore reduce nitrous oxide emissions from slurry applied to soil (Kool et al, 2006;Sánchez-Martín et al, 2017), which seems to be related with changes in pH and the corresponding reduction of NH 3 emission.…”
Section: Nutrient Balance and Effluent Compositionsupporting
confidence: 79%
“…Total N was determined by steam distillation (APHA, 2005) using an automatic analyser (2300 Kjeltec, Foss Analytical, Hilleroed, Denmark). Hippuric and benzoic acids were analysed directly in urine samples via high performance liquid chromatography (HPLC) on a Varian Pro Star 310 HPLC system (Varian Inc., Palo Alto, CA, USA) following the procedure described by Sánchez-Martín et al (2017).…”
Section: Chemical Analysis Of Feeds and Effluentsmentioning
confidence: 99%
“…Total Kjeldahl N (TKN) was determined using an automatic analyzer (2300 Kjeltec, Foss Analytical, Hilleroed, Denmark) according to [ 28 ]. Hippuric and benzoic acids were analyzed directly in urine via high performance liquid chromatography on a WATERS Alliance system (model 2695) following the procedure described by [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nitrous oxide emission factors (EFs) from urine, defined as the % of N input lost as N 2 O after subtracting background emissions, can be affected by variation in soil conditions driven by differences in climate, soil type, latitude and pasture management (Chadwick et al, ; Dijkstra et al, ). Animal diet can also alter N 2 O emissions factors due to impacts on urine composition (Ciganda et al, ; Sanchez‐Martin et al, ). As a result, EFs have been found to vary both spatially and temporally.…”
Section: Introductionmentioning
confidence: 99%